Pakistan : Second Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2001)
Pakistan showed good macroeconomic performance and structural reforms under the program supported by the Stand-By Arrangement. Executive Directors welcomed this development, and stressed the need for sustained implementation of firm macroeconomic policies, increased revenue collection effort, and a substantial reallocation of public expenditure toward poverty-reducing spending. They emphasized the need to improve governance, accelerate structural reforms, and strengthen the financial system. Directors agreed that the country has successfully completed the second review under the Stand-By Arrangement, and approved a waiver.